The Antiviral Effect of High-Molecular Weight Poly-Gamma-Glutamate against Newcastle Disease Virus on Murine Macrophage Cells. (30th December 2014) - Talactac, Melbourne; Lee, Jong-Soo; Moon, Hojin; Chowdhury, Mohammed Y. E.; Kim, Chul Joong
Abstract : This study demonstrates the capacity of HM- γ -PGA treatment to significantly protect murine macrophage cells (RAW 264.7 cells) against NDV infection. Such protection can be explained by the induction of antiviral state of HM- γ -PGA in RAW 264.7 cells via TLR4-mediated IRF-3, IRF-7, IFN- β, and IFN-related gene induction as shown in time-dependent changes in mRNA expression confirmed by polymerase chain reaction (PCR). Moreover, the present research also showed that HM- γ -PGA can induce proinflammatory cytokine secretion in RAW 264.7 as measured by enzyme-linked immunosorbent assay (ELISA). Therefore, our findings suggest that HM- γ -PGA can be a potential antiviral substance that can inhibit NDV infection through its stimulation of antiviral state on RAW 264.7 cells. These results have been consistent with the previous studies showing that HM- γ -PGA can protect RAW 264.7 cells and mice against influenza infection. However, it should be noted that although murine macrophage cells are susceptible to NDV, they are not the natural host cells of the virus; thus further in vivo and in vitro studies involving chicken and chicken immune cells are needed to fully assess the efficacy and applicability of HM- γ -PGA in the poultry industry.